Quantification of organic acids in beer by nuclear magnetic resonance (NMR)-based methods - Rodrigues, J. E. A. (2020)
The organic acids present in beer provide important information on the product's quality and history, determining organoleptic properties and being useful indicators of fermentation performance. NMR spectroscopy may be used for rapid quantification of organic acids in beer and different NMR-based methodologies are hereby compared for the six main acids found in beer (acetic, citric, lactic, malic, pyruvic and succinic). The use of partial least squares (PLS) regression enables faster quantification, compared to traditional integration methods, and the performance of PLS models built using different reference methods (capillary electrophoresis (CE), both with direct and indirect UV detection, and enzymatic essays) was investigated. The best multivariate models were obtained using CE/indirect detection and enzymatic essays as reference and their response was compared with NMR integration, either using an internal reference or an electrical reference signal (Electronic REference To access In vivo Concentrations, ERETIC). NMR integration results generally agree with those obtained by PLS, with some overestimation for malic and pyruvic acids, probably due to peak overlap and subsequent integral errors, and an apparent relative underestimation for citric acid. Overall, these results make the PLS-NMR method an interesting choice for organic acid quantification in beer.